Gyro stabilised vertical opening inspection and surveying system - Jarosz, Andrew; Langdon, James (The Reading Matrix Inc., 2007)
Vertical openings, particularly ore passes, created and utilised in underground mines are difficult to access, inspect and survey. However, they are frequently the crucial element of the ore flow system and their failure may have significant impact on performance and productivity of a mine. As in most cases there is no direct human access to ore passes, remote techniques must be used to perform inspections and surveys. Up-to-date, most inspection systems utilised a sensing pod suspended on a cable deployed from a winch. The suspended pod was usually equipped with illumination devices and video cameras. The analogue video signal was transmitted over data lines imbedded into a steel cable to a control unit located in the proximity of the winch. Stabilisation of the sensing pod and cameras was the main problem of the existing systems. They did not have either any surveying capabilities that allow for collection of metric information. The vertical opening inspection and surveying system, which is presently under development at the Western Australian School of Mines (Curtin University), provides inspection and surveying capabilities. The unique gyro system provides rotational stabilisation of the pod and allows for significant increase of data quality.